Dimensi Metrik Graf Hasil Kali Graf Lengkap Orde Dua terhadap Graf Sarang Lebah - Saskia Nurul Jannah; Hasmawati Basir; Naimah Aris (Jurnal Matematika, Statistika dan Komputasi, 2024)
Metric dimension is a concept in graph theory that has been developed in terms of the concept and its application. Let G be a connected graph and S be a vertex subset on connected graph G. The set S is called a resolving set for G if every vertex on graph G has a distinct representation of one to each other of S. A resolving set containing a minimum cardinality is called basis. The metric dimension on graph G is cardinality of basis on graph G, notated with dim (G). In this case, the cross-product graph will be used for the research. The aim of this research is to determine the metric dimension of the second order complete graph (K2) with honeycomb networks (HC(n)) cross-operation product. Utilizing mathematical induction, we generated dim(K2×HC(n)) = 3.